The complete chloroplast genome sequence of Camellia sinensis cv. Dahongpao: a most famous variety of Wuyi tea (Synonym: Thea bohea L.). Issue 1 (2nd January 2021) - Li, Li; Hu, Yunfei; Wu, Linhui; Chen, Rongbing; Luo, Shengcai
Abstract: Here, combining PacBio and Illumina sequencing data, we reported the complete chloroplast genome of the first Wuyi tea ( Bohea ), Camellia sinensis cv. Dahongpao (DHP) with very high economic value. The chloroplast genome was 157, 077 bp in length, with a large single copy (LSC) region of 86, 633 bp, a small single-copy (SSC) region of 18, 282 bp, separated by two inverted repeat (IR) regions of 26, 081 bp each. It contained a total of 137 genes, with an overall GC content of 37.29%. The phylogenetic analysis showed that DHP was sister to C. sinensis cv. Longjing .